2009
DOI: 10.1007/s11881-008-0020-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of gene DCDC2 in German dyslexics

Abstract: Dyslexia is a complex reading and writing disorder with a strong genetic component. In a German case-control cohort, we studied the influence of the suspected dyslexia-associated gene DCDC2. For the first time in a German cohort, we describe association of a 2445 basepair deletion, first identified in an American study. Evidence of association for three DCDC2 single nucleotide polymorphisms (rs807724, rs793862, rs807701), previously identified in German or American cohorts, was replicated. A haplotype of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 33 publications
2
76
1
Order By: Relevance
“…Replication of this SNP, along with expression and/or sequencing analyses to uncover its associated functional effects, would be desirable. We did not find significant support for association of reading and spelling with rs793862, the most widely genotyped polymorphism in DCDC2 association studies; though we did observe the same at-risk allele as in earlier studies 10,11,36,37 (the T-allele conferred a reading disadvantage of just 0.02 SD). Contradictory findings have been reported for this SNP: from nominally significant associations, 8,9 to associations specific only in the most severely affected families, 10 to the reverse effect (a nominally significant association in independent UK samples that disappeared when the sample was restricted to individuals with severe spelling difficulties 7 ), to no support for association of rs793862 to dyslexia in a cohort of US families.…”
Section: Discussioncontrasting
confidence: 97%
“…Replication of this SNP, along with expression and/or sequencing analyses to uncover its associated functional effects, would be desirable. We did not find significant support for association of reading and spelling with rs793862, the most widely genotyped polymorphism in DCDC2 association studies; though we did observe the same at-risk allele as in earlier studies 10,11,36,37 (the T-allele conferred a reading disadvantage of just 0.02 SD). Contradictory findings have been reported for this SNP: from nominally significant associations, 8,9 to associations specific only in the most severely affected families, 10 to the reverse effect (a nominally significant association in independent UK samples that disappeared when the sample was restricted to individuals with severe spelling difficulties 7 ), to no support for association of rs793862 to dyslexia in a cohort of US families.…”
Section: Discussioncontrasting
confidence: 97%
“…Most of the genetic associations with dyslexia cluster around the 5' end of the KIAA0319 gene and generally show the same allelic trends across independent studies (Francks et al, 2004, Cope et al, 2005Schumacher et al, 2007;Luciano et al, 2007;Paracchini et al, 2008;Couto et al, 2009;Dennis et al, 2009;Wilcke et al, 2009). Francks et al (2004) identified 1 main RD risk haplotype comprising 3 SNPs (rs4504469, rs2038137, and rs2143340) with a frequency of 12% in families from the United Kingdom and the United States.…”
Section: Introductionmentioning
confidence: 73%
“…Ludwig et al (2008) used both categorically and quantitatively related traits to investigate the association between RD and DCDC2 intron 2 deletion and short tandem repeat (STR) variants, but did not detect a significant association between RD and these genetic variants. In contrast, Wilcke et al (2009), studying an independent German sample, reported evidence for an association between the DCDC2 intron 2 deletion variant and a dyseidetic diagnostic subtype characterized by major impairment of visual perception. Lind et al (2010) recently reported a study supporting an association of 2 SNPs in DCDC2 with quantitative measures in Australian families that were unselected for reading impairment.…”
Section: Introductionmentioning
confidence: 92%
“…Table 5 Genes with Known Function from the List of Best Hits in Table 2. DCDC2 is thought to play a role in neuronal migration, and has been associated with dyslexia in multiple independent studies (e.g., Meng et al, 2005;Schumacher et al, 2006;Wilcke et al, 2009) (p values = .0003, .004, and <.05 respectively). It has been associated with variation in reading and spelling ability in a general population (p values <.001) (Lind et al, 2010), with inattention and hyperactivity/impulsivity symptoms of ADHD (Couto et al, 2009), and with the distribution of grey matter in language-related brain regions in healthy individuals (p < .01 for volumetric differences between genotype groups) (Meda et al, 2008).…”
Section: Discussionmentioning
confidence: 99%